Distributive Efficiency: Enhancing On-Time Delivery Through Accessibility and FIFO Integration - Soekirman, Atong (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this scientific article is to provide insight into strategies and steps that can be taken by companies to overcome such problems and improve the efficiency of their distribution systems. Thus, this article can contribute to the existing literature in the field of supply chain management, logistics, and overall business operations. The method used is qualitative by presenting the results in the literature derived from related scientific articles. Research findings are presented in the form of research reports or scientific articles that highlight the methodology, main findings, interpretation, and implications of the study. The final result of this scientific article makes a contribution from the perspective of the researcher. To achieve excellence in the distribution and delivery of goods, companies need to adopt a holistic approach and use the right technology. By taking into account findings from previous research, companies can improve their operational performance, reduce costs, and increase customer satisfaction through the implementation of efficient and innovative distribution strategies.